ANALISIS MANAJEMEN RANTAI PASOK BERAS DI KABUPATEN DEMAK - Kurniawati, Nurul Imani; Mege, Stacia Reviany; Werdani, Riandhita Eri (BISMA: Jurnal Bisnis dan Manajemen, 2020)
A well-managed supply chain flow will make the product distribution up to the final consumers runs effectively and efficiently. This study aimed to analyze the rice supply chain flow in Demak Regency, Central Java Province. Using a qualitative descriptive method, the authors conducted field observations, in-depth interviews, and focus group discussions with several parties as informants. The informants consisted of farmers, merchant collectors, rice grinders, wholesalers, retailers, and the Department of Agriculture and Trade Office officers. The results showed that the rice supply chain in Demak Regency starts from farmers to traders and mills, then to the wholesalers, retailers, Indonesian Bureau of Logistics, supermarkets, and final consumers. The government can encourage and facilitate every process to create effectiveness and efficiency in the rice supply chain in Demak Regency. Keywords: distribution, rice, supply chain